The Monetary Policy in a Dual Banking System, Islamic and Conventional Banks: Bibliometric Analysis - Pribadi, Dandi Tegas; Suprayitno, Eko; Prajawati, Maretha Ika (Gorontalo State University, 2025)
This study examines the bibliometric analysis of monetary policy in a dual banking system, encompassing Islamic and conventional banks. Monetary policy is a central bank instrument for managing economic stability through interest rate control, inflation regulation, and liquidity management. The study aims to identify publications related to monetary policy in the context of Islamic and conventional banks and to understand research trends in this field. The bibliometric analysis method was employed using VOSviewer software, with data sourced from the Dimensions database spanning 2015-2024. The findings indicate that the United States and Indonesia are the leading countries in terms of publication volume and total link strength. Additionally, the Journal of Islamic Accounting and Business is identified as the most influential journal in this area. Keywords such as Monetary Policy, Dual Banking System, and Islamic Banks frequently appear as dominant research themes. The most influential article is Aysan (2017), which analyzes interest rate sensitivity in Turkey's dual banking system. The study concludes that monetary policy plays a crucial role in both banking systems, with distinct transmission mechanisms. Future research is recommended to utilize broader datasets and integrate bibliometric analysis with qualitative or quantitative approaches to deepen the interpretation of interrelated research topics.